Resection of Gastrointestinal Metastases in Stage IV Melanoma: Correlation with Outcomes. Issue 11 (November 2016) - Prabhakaran, Sangeetha; Fulp, William J.; Gonzalez, Ricardo J.; Sondak, Vernon K.; Kudchadkar, Ragini R.; Gibney, Geoffrey T.; Weber, Jeffrey S.; Zager, Jonathan S.
The prognosis of patients with gastrointestinal (GI) melanoma metastases is poor. Surgery renders select patients disease free and/or palliates symptoms. We reviewed our single-institution experience of resection with GI melanoma metastases. A retrospective review was performed on patients who underwent surgery for GI melanoma metastases from 2007 to 2013. Fifty-four patients were identified and separated based on completeness of resection into curative 13 (24%) and palliative 41 (75.9%) groups. Thiry-six (63.2%) were symptomatic preoperatively with bleeding and/or obstruction/pain with 91.7 per cent achieving objective symptom relief. Thirty-day operative mortality was 0 per cent. The most common complication was wound infection (n = 5); major complications like anastomotic leak (n = 1) were uncommon. With a median follow-up of 9.5 months (range 0.2–75.8), median overall survival was not reached (curative) versus 9.53 months (palliative group). Median recurrence-free and progression-free survival after resection were 18.89 and 1.97 months in the curative versus palliative groups, respectively. On multivariate analysis, resection to no clinical evidence of disease (P = 0.012) and presence of single metastases (P = 0.031) were associated with improved overall survival. Surgery for GI metastases from melanoma provides symptomatic relief without major morbidity. Fewer metastases and curative resection were associated with improved survival.